Plasma plasminogen activator inhibitor-1 as a predictive marker of type 2 diabetic nephropathy in Egyptian patients - El-Saei; Mostafa M.M. Alomairi; Ashraf M. El- Kabeer; Sayed F.A Abd-Allah (Wolters Kluwer Medknow Publications, 2023)
Background The study investigates the relationship between Plasminogen activator inhibitor-1 (PAI-1) levels and the progression of diabetic nephropathy (DN). The fibrinolytic system is impaired in type 2 diabetes mellitus (DM), leading to elevated PAI-1 levels, increasing the potential for renal fibrosis and worsening nephropathy. Patients and methods The research involved 196 type 2 DM patients and 50 healthy control individuals divided into four groups based on Urinary albumin excretion (UAE). Results The diabetic group had significantly higher PAI-1 levels than the control group. The study also found that diabetic patients with macroalbuminuria had higher PAI-1 levels than the control group. Patients with higher UAE and PAI-1 levels had significantly higher serum creatinine concentrations. The study found a significant negative link with creatinine clearance and a significant positive correlation between PAI-1 and serum creatinine and 24-h urine albumin in terms of PAI-1. Conclusions There was a notable positive association with the 24-h UAE, suggesting that increases in PAI-1 were linked to a decline in renal function.